2006
DOI: 10.1039/b600771f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tetrabutylphosphonium cation on the physico-chemical properties of amino-acid ionic liquids

Abstract: Tetraalkylphosphonium-based amino-acid ionic liquids show lower viscosities and higher decomposition temperatures (>300 degrees C) than previously reported ammonium-based amino-acid ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(108 citation statements)
references
References 24 publications
1
107
0
Order By: Relevance
“…They are complementary to ionic liquids with amino-acid-based anions. [109][110][111] The acesulfamate and saccharinate ionic liquids described in the present study are hydrophilic, but their miscibility with organic solvents depends very much on the type of cation. Pernak and co-workers found that phosphonium acesulfamate ionic liquids are hydrophobic, although they are hygroscopic.…”
Section: Discussionmentioning
confidence: 99%
“…They are complementary to ionic liquids with amino-acid-based anions. [109][110][111] The acesulfamate and saccharinate ionic liquids described in the present study are hydrophilic, but their miscibility with organic solvents depends very much on the type of cation. Pernak and co-workers found that phosphonium acesulfamate ionic liquids are hydrophobic, although they are hygroscopic.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphonium-based AAILs as cellulose solvents in the presence of a cosolvent (Kagimoto et al 2006). The potentially less reactive novel [TBP][DMGly] was synthesized and also tested.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the development of eco-friendly and biocompatible ILs is urgently required. Amino acid ionic liquids (AAILs) are not only halogen free but also have lower viscosity than conventional ILs at room temperature (r.t.) (Kagimoto et al 2006;Jiang et al 2008). They have the potential to be an ideal solvents for cellulose and are expected to be compatible with a subsequent enzymatic hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, aspartic acid-and glutamic acid-derived ionic liquids were developed. [6][7][8] The structural features of them are functionalized dicarboxylic acid obtained from natural resources. The ionic structure is beneficial to dissolve them into ionic liquids.…”
mentioning
confidence: 99%